RETRIEVAL OF PM2.5 CONCENTRATIONS USING MODIS-DERIVED AEROSOL OPTICAL DEPTH IN HO CHI MINH CITY, VIETNAM - Van Manh, Nguyen; Dai Long, Nguyen; Thi Thu Ha, Hoang; Thi Kim Cuc, Luong (HNUE Journal of Science: Journal of Natural Sciences, 2026)
Air pollution characterized by fine particulate matter (PM2.5) has emerged as a critical environmental problem in Vietnam, particularly within densely populated metropolitan areas like Ho Chi Minh city. The integration of remote sensing (RS) and geographical information systems (GIS) offers a robust framework for monitoring PM2.5 due to its extensive spatial coverage, high temporal resolution, and cost-effectiveness. This study estimates ground-level PM2.5 concentrations by establishing a correlation between in-situ measurements from six monitoring stations and Aerosol Optical Depth (AOD) values retrieved from MODIS satellite imagery. The spatial, temporal, and seasonal dynamics of PM2.5 in Ho Chi Minh city during the 2020 – 2025 period. Results indicate that the highest concentrations are concentrated in central urban districts, averaging 24.0 μg/m³. During the rainy season, the average of PM2.5 concentration drops to 14.4 μg/m³. This seasonal reduction is primarily attributed to enhanced atmospheric dispersion and the wet deposition (rainwash). Overall, the study demonstrates that utilizing satellite-derived AOD provides a more comprehensive spatial understanding of PM2.5 distribution, thereby supporting evidence-based air quality management and sustainable urban planning.